Larva bicefala de Aegorhinus superciliosus (Guerin) (Coleoptera: Curculionidae) - Aguilera P, A.=700 1 Klein K, C.; Rebolledo R, R.
(Es, En)
Ilus., 18 ref.
Keywords: COLEOPTERA; CURCULIONIDAE; ZOOLOGIA; REGISTRO; CHILE; TERATOLOGIA; AEGORHINUS SUPERCILIOSUS; LARVA BICEFALA; REVISTA CHILENA DE ENTOMOLOGIA